Pengaruh Kecerdasan Emosional dan Beban Kerja Terhadap Turnover Intention (Studi Kasus Pada Kurir J&T Express Way Kandis, Bandar Lampung) - Lupika Sari; Iskandar Ali Alam (Komunitas Dosen Indonesia, 2025)
This research aims to determine the influence of Emotional Intelligence and workload on the desire to change jobs (turnover) among employees in the package delivery service section at J&T Express Way Kandis, Bandar Lampung. This research used a saturated sampling strategy, meaning that fifty respondents were taken from the entire population who could potentially become participants. The data collection method used is through distributing questionnaires and using primary and secondary data. The data analysis carried out included instrument testing and the analysis used was classical assumption testing using SPSS Version 30. This research model meets the requirements for classical assumption testing, including the absence of heteroscedasticity and multicollinearity, as well as normality assumptions. Both emotional intelligence and workload are characteristics that influence the desire to leave the organization, according to the findings of the partial test (t test). Simultaneously, it is revealed that both emotional intelligence and workload influence the desire to change jobs. This research shows that emotional intelligence and workload influence the desire to change jobs. Companies can manage employee emotions and workload in a balanced way to increase retention and create a comfortable work environment.